Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/438575a
|View full text |Cite
|
Sign up to set email alerts
|

Fruit bats as reservoirs of Ebola virus

Abstract: The first recorded human outbreak of Ebola virus was in 1976, but the wild reservoir of this virus is still unknown. Here we test for Ebola in more than a thousand small vertebrates that were collected during Ebola outbreaks in humans and great apes between 2001 and 2003 in Gabon and the Republic of the Congo. We find evidence of asymptomatic infection by Ebola virus in three species of fruit bat, indicating that these animals may be acting as a reservoir for this deadly virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
1,189
2
39

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,383 publications
(1,242 citation statements)
references
References 9 publications
12
1,189
2
39
Order By: Relevance
“…Bats are thought to have an important role in the maintenance of filoviruses in nature, but which bat species carry filoviruses and whether other species are involved are unknown 1,2 . Historical filovirus outbreaks originated in Central Africa and ranged in size from a few to more than 400 cases; these outbreaks were reasonably well controlled by quarantine and contact tracing.…”
mentioning
confidence: 99%
“…Bats are thought to have an important role in the maintenance of filoviruses in nature, but which bat species carry filoviruses and whether other species are involved are unknown 1,2 . Historical filovirus outbreaks originated in Central Africa and ranged in size from a few to more than 400 cases; these outbreaks were reasonably well controlled by quarantine and contact tracing.…”
mentioning
confidence: 99%
“…Studies of ZEBOV have identified bats as potentially being among the natural hosts for ebolaviruses 87 , and epidemiological evidence for MARV is also consistent with bats being the wildlife reservoirs of these viruses. The impact of these viruses on individual bats and bat populations is relatively unknown, but the consequences of filoviral infections in humans and non-human primates can be devastating: an acute disease with human mortality rates as high as 89% for sizeable outbreaks of either ZEBOV 88 or MARV 89 .…”
Section: Box 1 | Filovirus-disease Basicsmentioning
confidence: 85%
“…EBOV, SUDV, TAFV, and BDBV are known to spillover from wildlife and cause EVD in humans, while RESTV is not considered to be a human pathogen (Judson et al 2016). Three species of fruit bats have been found to be polymerase chain reaction (PCR) positive for EBOV (Leroy et al 2005), while other animals have been implicated as secondary hosts (Olival and Hayman 2014). These putative reservoir and secondary host species are present in Cameroon (Leroy et al 2005).…”
Section: Ebola Virusmentioning
confidence: 99%
“…Three species of fruit bats have been found to be polymerase chain reaction (PCR) positive for EBOV (Leroy et al 2005), while other animals have been implicated as secondary hosts (Olival and Hayman 2014). These putative reservoir and secondary host species are present in Cameroon (Leroy et al 2005). Serosurveys have found humans seropositive for filoviruses in Cameroon, predominantly those living in southern tropical rainforest (Gonzalez et al 1989;Kuhn 2008).…”
Section: Ebola Virusmentioning
confidence: 99%